THE EFFECT OF PEER TEACHING ON THE LEVEL OF UNDERSTANDING OF TURBO THROWING MATERIAL FOR ELEMENTARY SCHOOL CHILDREN - Ayu, Citra; Saputra, Yudha M; Dinangsit, Dinar (Universitas Negeri Medan, 2023)
Turbo throwing is a modification of javelin throwing intended for children where the series of movements begins with a throwing prefix and further motion. The students in general have not mastered the basic movements of turbo throwing. Children are out of place if they are taught to achieve high achievements in sports but instead they must be guided according to their physical and mental abilities as stated in teaching physical education in elementary schools must be adjusted to the level of student ability. The peer teaching learning model is a cooperative learning strategy where mutual respect and understanding are fostered among students working together. Peer teaching facilitates learning, students actively participate, and can solve problems together, so that an even distribution of understanding of the learning material provided can be achieved The purpose of this study was to determine the effect of the Peer Teaching learning method on the accuracy of the turbo throw of elementary school children. This research was conducted at State Elementary School 3 pegagan Kidul Cirebon Regency. By involving 9 students consisting of 2 male students and 7 female students. This study uses an experimental research method where the primary data source is the researcher who takes action and the students who receive the action, while the secondary data is in the form of documentation data. The results showed that the peer teaching learning method was able to improve students' understanding of turbo throwing learning material. The conclusion of the study states that in the subject of Physical Education and Health athletics turbo throwing numbers with peer teaching learning methods can improve student learning outcomes in class V SD Negeri 3 Pegagan Kidul, and is useful for adding to the learning process learning method innovation.